New Turbidimetric-Continuous Flow Injection Analysis Method for The Determination of Chlorpromazine HCl in Pharmaceutical Preparation Using Linear Array Ayah 5SX1-T-1D-CFI Analyser - Shakir, Issam (Iraqi Journal of Science, 2023)
A new turbidimetric-flow injection method is described for the determination of chlorpromazine HCl in pure and pharmaceutical preparation. The method is characterized by simplicity, sensitivity and fast, it is based on formation of ion pair compound between chlorpromazine HCl and Potassium hexacyanoferrate(III) in an acid medium for the formation of greenish yellow precipitate. This precipitate was determined using homemade Linear Array Ayah 5SX1-T-1D continuous flow injection analyser. Optimum concentrations of chemical reactants, physical instrumental conditions have been investigated. The linear dynamic range of chlorpromazine HCl was 3-30 mmol.L-1 while correlation coefficient (r) was 0.9929 and percentage linearity (%r2) C.O.D was 98.59%. Limit of Detection (S/N=3) 3×10-7 M/sample equivalent to 0.12 g/sample from the stepwise dilution of minimum concentration for the lowest concentration in the linear dynamic range of the calibration graph with R.S.D.% (n=6) < 2% for concentration 8 and 10 mmol.L-1. The method was applied successfully for the determination of chlorpromazine HCl in pharmaceutical drugs. A comparison was made between the developed method with the official method via the use of paired t-test. It shows that there were no significant differences between either methods. Therefore the newly developed method (K3[Fe(CN)6]-HCl-Chlorpromazine HCl) can be adopted as an alternative method for determination of Chlorpromazine HCl.